Investigating the impact of shopper personality on behaviour in immersive Virtual Reality store environments. (July 2021) - Schnack, Alexander; Wright, Malcolm J.; Elms, Jonathan
Abstract: The increasing availability of immersive Virtual Reality (VR) hardware in private households has opened up significant opportunities for innovations in online retailing. Online retailers can develop realistic, albeit simulated, three-dimensional retail environments that use immersive elements to create a more exciting online shopping experience. Nevertheless, to date, very little is known about how observed shopper behaviour in immersive VR store environments compares to existing knowledge in the physical or other online retail research literature. To that end, this paper focuses on human personality traits and whether these translate to familiar observations of in-store shopper behaviour. Specifically, the research examined the 'Big Five' personality traits – agreeableness, conscientiousness, extraversion, neuroticism, and openness to experience, and their impact on purchase behaviours such as product inspection time, proportion of private label purchases, and impulsive buying. It is further investigated how the purchase behaviours impact the outcomes of the shopping trip. The results revealed a variety of expected relationships between purchase metrics and the outcomes of the shopping trip; however, in stark contrast to the findings of extant studies, shopper personality did not show any impacts on the investigated purchase behaviours. Further research is needed to determine whether this failure to replicate past studies of shopper personality was, in fact, due to differences in the store environment or rather due to the moving from survey-based method of shopper data collection to naturalistic observation. Nonetheless, this finding has important implications for e-retailing strategies and market research practices. Graphical abstract: Image 1 Highlights: We study the relationship between 'Big Five' personality dimensions and shopper behaviour in an immersive Virtual Reality convenience store. No impacts of shopper personality on behavioural observations were found, which contradicts findings of existing shopper research studies. The findings imply that differences between physical and immersive Virtual Reality store environments may be responsible for this failure to replicate past studies. An alternative explanation are validity issues of survey methodology causing a gap between observational and subjective shopper data.